THE SINGING CHURCH: AN ANALYSIS OF VOCAL DEVIATIONS IN CONGREGATIONAL SINGING - A STUDY OF HKBP CONGREGATIONAL SINGING TECHNIQUES - Ruth Melody Misbow Siallagan; Mauly Purba; Vanesia Amelia Sebayang; Junita Batubara (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the policies of the Huria Kristen Batak Protestan (HKBP) Church regarding congregational singing practices during Sunday worship and to evaluate their implementation in order to identify an ideal model for improving the quality of congregational singing techniques. The primary issue addressed in this research is the prevalence of technical errors in congregational singing, such as inaccurate rhythm, poor intonation, unclear articulation, and uncontrolled vocal dynamics. These errors tend to occur repeatedly and systematically, which is suspected to be the result of oral tradition transmission without structured musical training. The research employs a descriptive qualitative method using a case study approach conducted in three HKBP church regions in North Sumatra: Tarutung, Pematangsiantar, and Medan. Data collection techniques include observation, in-depth interviews, and documentation. The findings indicate that although the HKBP possesses a rich legacy of church music, the implementation of policies related to congregational singing training remains uneven and lacks structure. Vocal technique training has not yet become an integral part of church programs, and congregational singing ability is largely shaped by worship habits without adequate pedagogical intervention. Oral tradition plays a significant role but is not sufficiently supported by formal musical approaches. Based on these findings, this study proposes an ideal model for developing congregational singing techniques that incorporates theological, musical, and inculturative aspects—taking into account the characteristics of Batak music and Christian spiritual values. This research is expected to make a meaningful contribution to enhancing the quality of worship in the HKBP context, particularly in the area of congregational singing as an expression of faith and a vital element of liturgy.